The Barriers to the Early Diagnosis of Multiple Myeloma in General Practice: A Narrative Review - Adamczyk, Aleksandra; Żeżawska, Karolina; Pal, Adrian; Cegiełka, Patryk; Sicińska, Maria Magdalena; Cienkowska, Alicja; Ślot, Marcin; Głowacka, Izabella; Szczęsny, Mikołaj; Katra, Małgorzata (Journal of Education, Health and Sport, 2026)
Background Multiple myeloma is a malignant hematological neoplasm characterized by the uncontrolled proliferation of monoclonal plasma cells in the bone marrow and monoclonal protein synthesis, resulting in numerous organ complications. Despite significant therapeutic advances early diagnosis still remains a critical factor in treatment efficacy. Diagnostic delays in multiple myeloma are among the longest of all hematological malignancies, often leading to irreversible organ damage. This issue is most prevalent in primary care, where low oncological vigilance and difficulties in interpreting early non-specific clinical manifestations often result in multiple consultations before a specialist referral. Aim The aim of this study is to analyze the factors contributing to diagnostic delays of multiple myeloma in general practice, evaluate the most common non-specific symptoms, and emphasize the importance of timely diagnosis. Material and Methods A narrative review was conducted using databases such as PubMed and Polish medical journals. The study analyzed publications concerning multiple myeloma patients, with a particular focus on the frequency of specific symptoms and the underlying causes of delayed diagnosis. Conclusions The average time to diagnose multiple myeloma is one of the longest in oncology. A key barrier is the non-specific clinical presentation, which leads to symptoms being attributed to more common chronic conditions. Consequently, nearly half of all patients require at least three primary care visits before receiving a preliminary diagnosis. Because diagnosis within three months correlates directly with longer remission, rapid intervention is vital. Improving the diagnostic process by routinely incorporating CRAB criteria and increasing oncological vigilance among primary care physicians are priority challenges to improve patient prognosis.